Modeling of a Surface Contact Stress for a Gear System Using Finite Element Method - F. R. M., Romlay; Asmizam, Mokhtar (Tech Science Press, 2008)
This paper presents a surface contact stress modeling of a spur gear using deterministic and Finite Element Method (FEM) via static stress analysis. Contact area or surface which is the critical part in gear system is needed for particular observation and investigation due to failure probability. Prior to this section, this research focus on understanding of stress distribution in spur gear system. A gear design is developed on CAD program by integration of equation control in order to have a flexibility of design intend. A FEM analyst is carried out to formulate and solve large systems of algebraic equations to obtain the relationship between the stress and force of the contact surface. Loading conditions and constraints are modeled due to affects of gear mechanism which influence the gear transmission. Result by FEM is compared with deterministic result for a validation procedure. Analysis of the results shows that the FEM have a good agreement comparing with the deterministic calculation.